Life Cycle Assessment of Ground Coffee and Comparison of Different Brewing Methods: A Case Study of Organic Arabica Coffee in Northern Thailand: DOI: 10.32526/ennrj.17.2.2019.16 - Phrommarat, Bhanupong (Environment and Natural Resources Journal, 2019)
Billions of cups of coffee are consumed worldwide every year with little regard for the wide range of environmental impacts arising at different stages of its life cycle. This study aimed to assess the environmental impacts of a single cup of hot, black coffee brewed from ground organic Arabica beans produced and consumed locally in the northern region of Thailand. Environmental impacts throughout its life cycle were assessed and the influences of different brewing methods were compared. Life cycle assessment (LCA) was implemented to evaluate the environmental performance of the product system. The results found that coffee cultivation is a major contributor to ecosystem damage in all brewing scenarios, particularly on land-use related midpoint indicators. Preparing the coffee by moka pot is especially energy intensive and showed a high impact score on human health. It also demonstrated resource damage categories in the brewing stage that were directly related to fossil-based electricity consumption. For other brewing scenarios, the upstream processes such as cultivation and bean processing were major contributors to environmental harm. According to the farming scenario analysis, the application of chemical fertilizers during conventional farming can aggravate the impact from the cultivation process on human health and resources, as compared to organic farming. This study comprises an initial stage of a coffee LCA study in Thailand. Hopefully, it can add to the body of information pertaining to the life cycle environmental impacts of coffee, a popular beverage product, aid decision-making, and increase attention on the importance of sustainable products.